PENDIDIKAN KARAKTER ANAK USIA DINI - Khaironi, Mulianah (PG-PAUD FKIP Universitas Hamzanwadi, 2017)
Character education in early childhood is an effort to cultivate good behavior in children, good behavior: in worship, being good citizen, interact with other people and environment, and useful for the success of his life. Character education is used in every environment in which the children located. The family environment is the first environment for child. The parents have a responsibility to inculcate good attitudes toward children. Then, they should not surrender childrens character education to teachers. Parents and teachers are models that will be imitated by them, both words and deeds. Character cultivation in children can be use through advice, habituation, exemplary, and reinforcement